Analysis of Corneal Spherical Aberrations in Chinese Bilateral Ectopia Lentis Patients - Jiahui Chen (Frontiers Media S.A., 2021)
Purpose: To analyze the anterior, posterior, and total corneal spherical aberrations (ASA, PSA, and TSA) in patients with Chinese bilateral ectopia lentis (EL).Methods: A cross-sectional study was conducted to evaluate corneal spherical aberration (CSA) using a Pentacam system at the 6-mm optical zone. Axial length, keratometry, astigmatism, and corneal asphericity were also determined.Results: This study included 247 patients (420 eyes) with a mean age of 18.1 years. The values of ASA, PSA, and TSA were 0.136 ± 0.100 μm, −0.118 ± 0.030 μm, and 0.095 ± 0.095 μm, respectively. In the EL patients with Marfan syndrome (MFS), ASA and TSA were significantly lower than in the non-MFS patients (0.126 ± 0.094 μm vs. 0.155 ± 0.107 μm, P = 0.004 for ASA; 0.085 ± 0.091 μm vs. 0.114 ± 0.099 μm, P = 0.003 for TSA), whereas PSA was not significantly different (P = 0.061). The values of ASA and TSA were significantly higher in the patients with EL aged ≥ 40 years old than in younger patients, whereas ASA and PSA were lower in patients aged <10 years old than in older patients (all P < 0.05). In the multiple linear regression analysis, age, keratometry, astigmatism, anterior asphericity, higher-order aberration (HOA), and lower-order aberration (LOA) were positively or negatively correlated with TSA in the patients with EL (r = 0.681, P < 0.001).Conclusions: Corneal spherical aberration was low in the patients with EL especially for MFS and tended to increase with aging. Preoperatively, individual measurement of CSA was necessary for bilateral EL patients with MFS.